2017
DOI: 10.5147/pggb.v1i1.148
|View full text |Cite
|
Sign up to set email alerts
|

The ‘PI 438489B’ by ‘Hamilton’ SNP-Based Genetic Linkage Map of Soybean [Glycine max (L.) Merr.] Identified Quantitative Trait Loci that Underlie Seedling SDS Resistance

Abstract: Soybeans [Glycine max (L.) Merr.] are susceptible to many diseases including fungal diseases such as soybean sudden death syndrome (SDS). Several studies reported SDS resistance quantitative trait loci (QTL) on the soybean genome using different recombinant inbred line (RIL) populations and low density genetic linkage maps. High density exclusively single nucleotide polymorphisms-based (SNP-based) maps were not yet reported in soybean. The objectives of this study were (1) to construct a high density SNP-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…In comparison with the alternative allele, the desired allele of this locus may reduce the disease severity by 10% (Figure a). An SDS resistance QTL has been previously reported at this genomic region (Abdelmajid et al ., ). Further analysis pinpointed ss715584189_T_C to the coding region of stress‐induced receptor‐like kinase gene 1 ( SIK1 ) (Figure b and Table ).…”
Section: Resultsmentioning
confidence: 97%
“…In comparison with the alternative allele, the desired allele of this locus may reduce the disease severity by 10% (Figure a). An SDS resistance QTL has been previously reported at this genomic region (Abdelmajid et al ., ). Further analysis pinpointed ss715584189_T_C to the coding region of stress‐induced receptor‐like kinase gene 1 ( SIK1 ) (Figure b and Table ).…”
Section: Resultsmentioning
confidence: 97%
“…The current study along with previous QTL mapping studies have identified 33 genetic regions on 18 chromosomes with QTL for partial resistance to P. sojae [ 33 , 39 50 , 52 , 56 , 61 ]. Of the 33 regions, four are coincident with Rps -genes [ 9 , 10 , 12 , 15 , 63 ] five are coincident with QTL for resistance to Sudden Death Syndrome [ 89 93 ], root disease caused by members of the fungus Fusarium viguliforme , 11 are coincident with QTL/genes for resistance to Soybean Cyst Nematode [ 94 103 ], and 11 are coincident with QTL for resistance to the necrotrophic fungal pathogen S. sclerotiorum causing Sclerotinia stem rot [ 59 , 62 , 104 , 105 ]. The coincidence of QTL for partial resistance to P. sojae with QTL and R -genes for resistance to pathogens with varied lifestyles provides evidence that partial resistance is likely conferred through a variety of different mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…In the vicinity of these identified SNPs, there were some QTLs reported to response to biotic stress. For example, SCN 19-1, SCN 19-2, SCN 19-4, SCN 33-7, SCN 44-5, SCN 18-1 , and SCN 37-1 have been reported to resistant to soybean cyst nematode ( Yue et al, 2001 ; Guo et al, 2006 ; Vuong et al, 2010 ; Jiao et al, 2015 ); SDS 13-1 was associated with resistant to soybean fungi disease sudden death syndrome (SDS) ( Abdelmajid et al, 2012 ); Japanese beetle resistance 1-4 was associated with herbivory pest Japanese beetles resistance ( Yesudas et al, 2010 ); Phytoph 5-3 was related to Phytophthora sojae infection ( Wu et al, 2011 ); Rag 3-2 associated with aphid resistance( Zhang et al, 2009 ); Asian Soybean Rust 2-4 resisted to fungal pathogen Phakopsora pachyrhizi ( Harris et al, 2015 ); Peanut root-knot nematode 2-2 was associated with resistance to peanut root-knot nematode in soybean ( Tamulonis et al, 1997 ).…”
Section: Resultsmentioning
confidence: 99%